Beneficial insects are associated with botanically rich margins with trees on small farms - Sarah E. J. Arnold (Nature Portfolio, 2021)
Abstract Beneficial insect communities on farms are influenced by site- and landscape-level factors, with pollinator and natural enemy populations often associated with semi-natural habitat remnants. They provide ecosystem services essential for all agroecosystems. For smallholders, natural pest regulation may be the only affordable and available option to manage pests. We evaluated the beneficial insect community on smallholder bean farms (Phaseolus vulgaris L.) and its relationship with the plant communities in field margins, including margin trees that are not associated with forest fragments. Using traps, botanical surveys and transect walks, we analysed the relationship between the floral diversity/composition of naturally regenerating field margins, and the beneficial insect abundance/diversity on smallholder farms, and the relationship with crop yield. More flower visits by potential pollinators and increased natural enemy abundance measures in fields with higher plant, and particularly tree, species richness, and these fields also saw improved crop yields. Many of the flower visitors to beans and potential natural enemy guilds also made use of non-crop plants, including pesticidal and medicinal plant species. Selective encouragement of plants delivering multiple benefits to farms can contribute to an ecological intensification approach. However, caution must be employed, as many plants in these systems are introduced species.